Simplified FEM modelling for the collapse assessment of a masonry vault - Pierluigi Olmati; Konstantinos Gkoumas; Franco Bontempi (Fracture and Structural Integrity)
This study is motivated from the collapse of an old masonry building in the Southern Italy. FEM analyses are carried out focusing on the influence of the contrasting wall on the stability of the vault. In the analyses, the structure is subjected to a damage scenario on the contrasting wall due to a demolition project, and the consequence of the damage is evaluated using the explicit dynamic simulation made by Ls-Dyna. A micro modelling technique (discrete FEM model) is adopted to model the masonry: the mortar is modelled by contact surfaces between the masonry units, which are explicitly modelled by blocks of meshes. This modelling technique is proven to be effective to predict the collapse behavior of the structure.